AÇÃO DE GIBERELINAS E CITOCININAS NA GERMINAÇÃO DE SEMENTES DE LARANJA AZEDA - Leonel, Sarita; Ono, Elizabeth Orika; Rodrigues, João Domingos (REVISTA DE AGRICULTURA, 2015)
AÇÃO DE GIBERELINAS E CITOCININAS NA GERMINAÇÃO DE SEMENTES DE LARANJA AZEDA